2021
DOI: 10.1002/jbm.a.37289
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the antimicrobial properties of cerium‐doped bioactive glasses

Abstract: Cerium-doped bioactive glasses (Ce-BGs) are implant materials that present high biocompatibility, modulate the levels of reactive oxygen species, and exert antimicrobial activity. The potential of BGs, 45S5, and K50S derived glasses doped with CeO 2 (1.2, 3.6, and 5.3 mol%) to inhibit the growth of pathogen microbes was thoroughly investigated according to the ISO 22196:2011 method properly adapted. A significant reduction of the E. coli charge was detected in all glasses, including the BGs without cerium. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 44 publications
1
8
0
Order By: Relevance
“…Moreover, the bacterial viability was evaluated after cultivation in the presence of scaffolds loaded with VAN. The results obtained (Figure 9) suggested an intrinsic antimicrobial effect of the samples similar to the data reported in the literature [49]. It was interesting to note a strong decrease in the microbial cells viability and ability to develop colonies in the case of bacteria seeded on S1Ce and S3Ce.…”
Section: Antibacterial Activitysupporting
confidence: 86%
See 1 more Smart Citation
“…Moreover, the bacterial viability was evaluated after cultivation in the presence of scaffolds loaded with VAN. The results obtained (Figure 9) suggested an intrinsic antimicrobial effect of the samples similar to the data reported in the literature [49]. It was interesting to note a strong decrease in the microbial cells viability and ability to develop colonies in the case of bacteria seeded on S1Ce and S3Ce.…”
Section: Antibacterial Activitysupporting
confidence: 86%
“…Youness et al [48] reported that the increase in cerium content in phosphate glasses enhanced their antibacterial activity against E. coli and S. aureus. Raimondi et al [49] studied the antibacterial activity of cerium doped BGs up to a 5.3 mol% content and observed that this activity is not directly associated with the presence of cerium, and it is dependent on the change of pH due to glass dissolution. Goh et al [50] reported the lack of antibacterial activity of polylactic acid/chitosan nanofibers decorated with cerium-containing bioactive glasses against E. coli, probably due to the slow release of ions from the glass composition and/or the small quantity of the glass adsorbed onto the nanofibers.…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…Similarly, various metal ions have been doped into BG to enhance their therapeutic behavior. For example, BG doped with Ag, 48 Cu, 49–51 Zn, 15 Ce 52 and Ga 17 showed antibacterial properties, Ga doping showed wound healing properties 53–54 and Ce doping revealed pro‐osteogenic potential 53 …”
Section: Resultsmentioning
confidence: 99%
“…Bioactive glasses (BGs) find application in medicine as bone fillers, scaffolds, and implant coatings due to their ability to stimulate bone regeneration; , since the development of the first BG (45S5 Bioglass), their therapeutic use has expanded significantly, supporting and/or generating many biomedical applications. BGs are particularly versatile materials, and a variation of their forms (powders, coatings, 3D-scaffolds, and fibers) and compositions (addition of therapeutic inorganic ions, TIIs) have been shown to improve a range of relevant properties such as osteogenesis, angiogenesis, antibacterial activity, and cementogenesis. , …”
Section: Introductionmentioning
confidence: 99%
“…Our research group has investigated the effect of the addition of TIIs to BGs, , with a focus on the antioxidant properties and therapeutic applications of cerium-doped BGs (Ce-BGs). , To elucidate the redox behavior (Ce 3+ /Ce 4+ ratio) of Ce-BGs, we performed studies with X-ray photoelectron spectroscopy (XPS) and near-edge X-ray absorption spectroscopy; the same study was also carried out on Ce-BGs after enzymatic-like or enzyme-mimetic tests were performed with the aim of accurately assessing the evolution of the Ce 3+ /Ce 4+ ratio. , Alginate-treated Ce-BGs were also studied to verify the maintenance of the Ce 3+ /Ce 4+ ratio . Ce-BGs present antioxidant, antibacterial, osteogenic, and angiogenic properties and are promising therapeutic options for wound healing and tissue repair. , …”
Section: Introductionmentioning
confidence: 99%